Photothermal effects of NaYF4:Yb,Er@PE3@Fe3O4 superparamagnetic nanoprobes in the treatment of melanoma - Wang X (Dove Medical Press, 2019)
Xue Wang,1 Chunyang Kang,2 Ying Pan,1 Rihua Jiang31Department of Obstetrics & Gynecology, China–Japan Union Hospital of Jilin University, Changchun, People’s Republic of China; 2Department of Neurology, China–Japan Union Hospital of Jilin University, Changchun, People’s Republic of China; 3Department of Dermatology, China–Japan Union Hospital of Jilin University, Changchun, People’s Republic of ChinaObjective: The study aimed to synthesize superparamagnetic NaYF4:Yb,Er@PE3@Fe3O4 upconversion nanoprobes and to study their photothermal effects for the treatment of malignant melanoma.Methods: Morphological characteristics of the synthesized nanoprobes were examined by scanning electron microscopy. Their biocompatibility and biodistribution profiles were assessed through blood routine/biochemistry tests and the inductively coupled plasma/optical emission spectrometry-based analysis of tissue metal elements. Their photothermal conversion efficiency and their potential as contrast agents for upconversion luminescence (UCL)/magnetic resonance imaging (MRI) dual-modal imaging were tested. Efficacy in photothermal therapy, which was achieved by combining nanoprobes with near-infrared (NIR) irradiation, was evaluated in both A375 cell line and BALB/c mice models. The underlying mechanisms were interrogated by molecular approaches including the MTT assay, flow cytometry, semiquantitative PCR, western blot, and immunohistochemistry.Results: 1) Our synthesized NaYF4:Yb,Er@PE3@Fe3O4 nanoprobes exhibited a uniform cubic morphology with a diameter of ∼50 nm. Subcutaneous administration led to no severe, long-lasting adverse effects in mice, possibly due to complete removal of these nanomaterials within one month. 2) Our nanoprobes possessed superior photothermal conversion efficiency and strong contrasting effects during UCL/MRI dual-modal imaging, corroborating their applications in imaging-guided photothermal therapy. 3) Combinatorial treatment of these nanoprobes with NIR irradiation induced profound apoptosis/necrosis in A375 cells. Similarly, the same treatment modality led to strong therapeutic effects in BALB/c mice implanted with A375 tumor xenografts. Mechanistic studies suggested an involvement of heat shock protein 70 in mediating the observed antitumor effects of our nanoprobes.Conclusion: Our study describes a convenient method to synthesize a new type of superparamagnetic upconversion nanoprobes, which possess high biocompatibility and can be used in imaging-guided photothermal therapy for the treatment of malignant melanoma. Importantly, our findings will promote clinical applications of NaYF4:Yb,Er@PE3@Fe3O4 as novel theranostic agents in treating melanoma and many other tumors.Keywords: upconversion nanoparticles, near infrared, photothermal therapy, melanoma, heat shock protein 70